2017
DOI: 10.1001/jamasurg.2017.0831
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Analgesics Commonly Unused After Surgery

Abstract: Importance Prescription opioids play an important role in the treatment of post-operative pain, yet unused opioids may be diverted for non-medical use and contribute to opioid-related injuries and deaths. Objective To quantify how commonly post-operative opioids are unused, why they remain unused, and practices regarding their storage and disposal after surgery. Evidence Review We searched PubMed, EMBASE, and Cochrane Central Register of Controlled Trials from inception to 18 October 2016 for studies descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
662
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 760 publications
(679 citation statements)
references
References 28 publications
16
662
1
Order By: Relevance
“…Unlike the 1960s, when heroin was the initial opioid in more than 80% of abusers, in the 2000s, prescription opioids were the gateway opioid in 75% of abusers . Seventy percent of intravenous heroin users in New York City reported nonmedical use of prescription opioids prior to first use of heroin, and 41% to 54% of people who misused opioids in 2014 and 2015 obtained prescription opioids free from friends or family …”
Section: Discussionmentioning
confidence: 99%
“…Unlike the 1960s, when heroin was the initial opioid in more than 80% of abusers, in the 2000s, prescription opioids were the gateway opioid in 75% of abusers . Seventy percent of intravenous heroin users in New York City reported nonmedical use of prescription opioids prior to first use of heroin, and 41% to 54% of people who misused opioids in 2014 and 2015 obtained prescription opioids free from friends or family …”
Section: Discussionmentioning
confidence: 99%
“…A colorectal ERP intervention which included epidural analgesia resulted in an increase in the use of opioid-free anesthesia and multimodal analgesia but did not decrease discharge opioid prescriptions 27. It is well recognized that opioid over-prescription occurs regularly after surgery among almost all surgical specialties and opioids are not regularly prescribed in a patient-specific manner to postoperative patients28–30 and up to 71% of these opioid pills go unused 30. Though the use of regional techniques may reduce perioperative opioid use, it cannot be utilized in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in ERAS for colorectal surgery showed that despite a reduction in inpatient postoperative opioids as a result of consistent compliance with multimodal and regional analgesia, patients were just as likely to be prescribed opioids at hospital discharge. 18 These findings, described by others as well, were primarily attributed to systems-level failures in time-of-discharge communication, prescription practices, 4,19 and patient follow-up coordination.…”
mentioning
confidence: 86%